Pulling teeth or pulling together? Time to improve antibiotic prescribing in dentistry - Daphne Yii; Yvonne Peijun Zhou; Shimin Jasmine Chung (Annals, Academy of Medicine, Singapore, 2025)
Antibiotic use in third molar (3M) surgeries is commonplace despite a growing body of evidence showing that routine prophylactic antibiotics offer little benefit in healthy patients. It also fuels the global public health crisis of antimicrobial resistance (AMR). This practice appears to remain deeply entrenched worldwide and is believed to be significantly caused by behavioural barriers.1 It is perceived and accepted that antibiotics reduce the likelihood of a post-procedure infection, but clinicians may be blindsided to the associated risks. In 3M surgeries, the number needed to treat (NNT) is 19, which is a relatively high NNT.2 This implies that a significant number of healthy patients may potentially experience adverse effects from unnecessary antibiotic exposure.